Neuroradiologic, Clinical, and Genetic Characterization of Cerebellar Heterotopia: A Pediatric Multicentric Study - Pasca, Ludovica; Arrigoni, Filippo; Romaniello, Romina; Severino, Maria Savina; Politano, Davide; D’Abrusco, Fulvio; Garau, Jessica; Giorgis, Valentina De; Carpani, Adriana; Signorini, Sabrina; Orcesi, Simona; D’Arco, Felice; et al. (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: Cerebellar heterotopia (CH) is a neuroradiologic abnormality that is poorly reported and investigated in the literature. It can be observed as an isolated finding, but it has been mainly reported in the context of cerebellar dysgenesis and syndromic conditions. This study aims to provide a comprehensive neuroradiologic, clinical, and genetic characterization of a cohort of pediatric patients with CH.MATERIALS AND METHODS: Patients with a diagnosis of CH were systematically selected from the neuroimaging databases of the 4 Italian centers participating in this retrospective study. For each patient, information regarding demographic, clinical, genetic, and neuroradiologic data was collected.RESULTS: Thirty-two pediatric patients were recruited and subdivided into 2 groups: patients with isolated CH and/or cerebellar malformations (n = 18) and patients with CH associated with cerebral malformations (n = 14). Isolated CH consistently showed a peripheral subcortical localization in the inferior portion of cerebellar hemispheres, with either unilateral or bilateral distribution. Ten patients belonging to the second group had a diagnosis of CHARGE syndrome, and their nodules of CH were mainly but not exclusively bilateral, symmetric, located in the peripheral subcortical zone and the inferior portion of the cerebellar hemispheres. The remaining 4 patients of the second group showed either bilateral or unilateral CH, located in both the peripheral cortex and deep white matter and the superior and inferior portions of cerebellum. Patients with isolated CH showed a high prevalence of language development delay; neurodevelopmental disorders were the most represented clinical diagnoses. Recurring features were behavioral problems and motor difficulties. A conclusive genetic diagnosis was found in 18/32 patients.CONCLUSIONS: We found distinctive neuroradiologic patterns of CH. Genetic results raise the possibility of a correlation between cerebellar morphologic and functional developmental disruption, underscoring the importance of CH detection and reporting to orient the diagnostic path.ASDautism spectrum disorderCCcorpus callosumCHcerebellar heterotopiaIVHinferior vermian hypoplasiaWESwhole exome sequencing